Design, synthesis and biological evaluation of immunostimulating mannosylated desmuramyl peptides - Ribić, Rosana; Stojković, Ranko; Milković, Lidija; Antica, Mariastefania; Cigler, Marko; Tomić, Srđanka (Beilstein Journal of Organic Chemistry, 2019)
Muramyl dipeptide is the minimal structure of peptidoglycan with adjuvant properties. Replacement of the N-acetylmuramyl moiety and increase of lipophilicity are important approaches in the preparation of muramyl dipeptide analogues with improved pharmacological properties. Mannose receptors present on immunocompetent cells are pattern-recognition receptors and by mannose ligands binding they affect the immune system. Here we present the design, synthesis and biological evaluation of novel mannosylated desmuramyl peptide derivatives. Mannose was coupled to dipeptides containing a lipophilic adamantane on N- or C-terminus through a glycolyl or hydroxyisobutyryl linker. Adjuvant activities of synthesized compounds were investigated in the mouse model using ovalbumin as an antigen. Their activities were compared to the previously described mannosylated adamantane-containing desmuramyl peptide and peptidoglycan monomer. Tested compounds exhibited adjuvant activity and the strongest enhancement of IgG production was stimulated by compound 21 (Man-OCH2-ᴅ-(1-Ad)Gly-ʟ-Ala-ᴅ-isoGln).
Keywords: adamantane; adjuvant activity; desmuramyl peptide; mannose

(untitled) - Awate, S.; Babiuk, L. A.; Mutwiri, G. (Front. Immunol., 2013)

(untitled) - Nielsen, A. E.; Hantho, J. D.; Mancini, R. J. (Future Med. Chem., 2017)

(untitled) - Traub, S.; von Aulock, S.; Hartung, T.; Hermann, C. (J. Endotoxin Res., 2006)

(untitled) - Kingeter, L. M.; Lin, X. (Cell. Mol. Immunol., 2012)

(untitled) - Ogawa, C.; Liu, Y.-J.; Kobayashi, K. S. (Curr. Bioact. Compd., 2011)

(untitled) - Lauro, M. L.; D’Ambrosio, E. A.; Bahnson, B. J.; Grimes, C. L. (ACS Infect. Dis., 2017)

(untitled) - Maekawa, S.; Ohto, U.; Shibata, T.; Miyake, K.; Shimizu, T. (Nat. Commun., 2016)

(untitled) - Keglević, D.; Ladešić, B.; Tomašić, J.; Valinger, Z.; Naumski, R. (Biochim. Biophys. Acta, Gen. Subj., 1979)

(untitled) - Halassy, B.; Krstanović, M.; Frkanec, R.; Tomašić, J. (Vaccine, 2003)

(untitled) - Tada, H.; Aiba, S.; Shibata, K.-I.; Ohteki, T.; Takada, H. (Infect. Immun., 2005)

(untitled) - Habjanec, L.; Halassy, B.; Tomašić, J. (Int. Immunopharmacol., 2010)

(untitled) - Rubino, S. J.; Magalhaes, J. G.; Philpott, D.; Bahr, G. M.; Blanot, D.; Girardin, S. E. (Innate Immun., 2013)

(untitled) - Gobec, M.; Tomašič, T.; Štimac, A.; Frkanec, R.; Trontelj, J.; Anderluh, M.; Mlinarič-Raščan, I.; Jakopin, Ž. (J. Med. Chem., 2018)

(untitled) - Gobec, M.; Mlinarič-Raščan, I.; Sollner Dolenc, M.; Jakopin, Ž. (Eur. J. Med. Chem., 2016)

(untitled) - Meyers, P. A. (Expert Rev. Anticancer Ther., 2009)

(untitled) - Dzierzbicka, K.; Kolodziejezyk, A. M. (Pol. J. Chem., 2003)

(untitled) - Jakopin, Ž.; Gobec, M.; Mlinarič-Raščan, I.; Sollner Dolenc, M. (J. Med. Chem., 2012)

(untitled) - Khan, F.-A.; Ulanova, M.; Bai, B.; Yalamati, D.; Jiang, Z.-H. (Eur. J. Med. Chem., 2017)

(untitled) - Vranešić, B.; Tomašić, J.; Smerdel, S.; Kantoci, D.; Benedetti, F. (Helv. Chim. Acta, 1993)

(untitled) - Ribić, R.; Habjanec, L.; Vranešić, B.; Frkanec, R.; Tomić, S. (Croat. Chem. Acta, 2011)

(untitled) - Ribić, R.; Habjanec, L.; Vranešić, B.; Frkanec, R.; Tomić, S. (Chem. Biodiversity, 2012)

(untitled) - Geijtenbeek, T. B. H.; Gringhuis, S. I. (Nat. Rev. Immunol., 2009)

(untitled) - Gazi, U.; Martinez-Pomares, L. (Immunobiology, 2009)

(untitled) - White, K. L.; Rades, T.; Furneaux, R. H.; Tyler, P. C.; Hook, S. (J. Pharm. Pharmacol., 2006)

(untitled) - Smrdel, P.; Grabnar, I.; Locatelli, I.; Černe, M.; Andrenšek, S.; Kovačič, N.; Kristl, A.; Bogataj, M.; Urleb, U.; Mrhar, A. (Drug Dev. Ind. Pharm., 2009)

(untitled) - Willems, M. M. J. H. P.; Zom, G. G.; Meeuwenoord, N.; Khan, S.; Ossendorp, F.; Overkleeft, H. S.; van der Marel, G. A.; Filippov, D. V.; Codée, J. D. C. (ChemMedChem, 2016)

(untitled) - Yang, R.; Xu, J.; Xu, L.; Sun, X.; Chen, Q.; Zhao, Y.; Peng, R.; Liu, Z. (ACS Nano, 2018)

(untitled) - Kramer, S.; Langhanki, J.; Krumb, M.; Opatz, T.; Bros, M.; Zentel, R. (Macromol. Biosci., 2019)

(untitled) - Raymond, J. B.; Mahapatra, S.; Crick, D. C.; Pavelka, M. S., Jr (J. Biol. Chem., 2005)

(untitled) - Chen, K.-T.; Huang, D.-Y.; Chiu, C.-H.; Lin, W.-W.; Liang, P.-H.; Cheng, W.-C. (Chem. – Eur. J., 2015)

(untitled) - Ribić, R.; Kodrin, I.; Biljan, I.; Paurević, M.; Tomić, S. (Struct. Chem., 2019)

(untitled) - Clariana, J.; Garcı́a-Granda, S.; Gotor, V.; Gutiérrez-Fernández, A.; Luna, A.; Moreno-Mañas*, M.; Vallribera, A. (Tetrahedron: Asymmetry, 2000)

(untitled) - Kaya, E.; Sonmez, F.; Kucukislamoglu, M.; Nebioglu, M. (Chem. Pap., 2012)

(untitled) - Ribić, R.; Kovačević, M.; Petrović-Peroković, V.; Gruić-Sovulj, I.; Rapić, V.; Tomić, S. (Croat. Chem. Acta, 2010)

(untitled) - Tomašić, J.; Hanzl-Dujmović, I.; Špoljar, B.; Vranešić, B.; Šantak, M.; Jovičić, A. (Vaccine, 2000)

(untitled) - Ribić, R.; Habjanec, L.; Frkanec, R.; Vranešić, B.; Tomić, S. (Chem. Biodiversity, 2012)

(untitled) - Štimac, A.; Šegota, S.; Dutour Sikirić, M.; Ribić, R.; Frkanec, L.; Svetličić, V.; Tomić, S.; Vranešić, B.; Frkanec, R. (Biochim. Biophys. Acta, Biomembr., 2012)

(untitled) - Štimac, A.; Šekutor, M.; Mlinarić-Majerski, K.; Frkanec, L.; Frkanec, R. (Molecules, 2017)

(untitled) - Car, Ž.; Kodrin, I.; Požar, J.; Ribić, R.; Kovačević, D.; Peroković, V. P. (Tetrahedron, 2013)

(untitled) - Yip, H. C.; Karulin, A. Y.; Tary-Lehmann, M.; Hesse, M. D.; Radeke, H.; Heeger, P. S.; Trezza, R. P.; Heinzel, F. P.; Forsthuber, T.; Lehmann, P. V. (J. Immunol., 1999)

(untitled) - Ioannou, X. P.; Gomis, S. M.; Karvonen, B.; Hecker, R.; Babiuk, L. A.; van Drunen Littel-van den Hurk, S. (Vaccine, 2002)

(untitled) - Magalhaes, J. G.; Fritz, J. H.; Le Bourhis, L.; Sellge, G.; Travassos, L. H.; Selvanantham, T.; Girardin, S. E.; Gommerman, J. L.; Philpott, D. J. (J. Immunol., 2008)

(untitled) - Girardin, S. E.; Boneca, I. G.; Viala, J.; Chamaillard, M.; Labigne, A.; Thomas, G.; Philpott, D. J.; Sansonetti, P. J. (J. Biol. Chem., 2003)

(untitled) - Traub, S.; von Aulock, S.; Hartung, T.; Hermann, C. (J. Endotoxin Res., 2006)

(untitled) - Tukhvatulin, A. I.; Dzharullaeva, A. S.; Tukhvatulina, N. M.; Shcheblyakov, D. V.; Shmarov, M. M.; Dolzhikova, I. V.; Stanhope-Baker, P.; Naroditsky, B. S.; Gudkov, A. V.; Logunov, D. Y.; Gintsburg, A. L. (PLoS One, 2016)

(untitled) - Roychowdhury, A.; Wolfert, M. A.; Boons, G.-J. (ChemBioChem, 2005)

(untitled) - Tom, J. K.; Albin, T. J.; Manna, S.; Moser, B. A.; Steinhardt, R. C.; Esser-Kahn, A. P. (Trends Biotechnol., 2019)

(untitled) - van Haren, S. D.; Dowling, D. J.; Foppen, W.; Christensen, D.; Andersen, P.; Reed, S. G.; Hershberg, R. M.; Baden, L. R.; Levy, O. (J. Immunol., 2016)

(untitled) - Yan, H.; Kamiya, T.; Suabjakyong, P.; Tsuji, N. M. (Front. Immunol., 2015)

(untitled) - Glaffig, M.; Stergiou, N.; Hartmann, S.; Schmitt, E.; Kunz, H. (ChemMedChem, 2018)

(untitled) - Opanasopit, P.; Sakai, M.; Nishikawa, M.; Kawakami, S.; Yamashita, F.; Hashida, M. (J. Controlled Release, 2002)

(untitled) - Habjanec, L.; Frkanec, R.; Halassy, B.; Tomašić, J. (J. Liposome Res., 2006)

(untitled) - Behr, M. A.; Divangahi, M. (Curr. Opin. Microbiol., 2015)